Cost Effectiveness of Malaria Interventions from Preelimination through Elimination: a Study in Iran. - Mohsen Rezaei-Hemami; Ali Akbari-Sari; Ahmad Raiesi; Hassan Vatandoost; Reza Majdzadeh (Tehran University of Medical Sciences, 2014)
Background: Malaria still is considered as a public health problem in Iran. The aim of the National Malaria Control Department is to reach the elimination by 2024. By decreasing the number of malaria cases in preelimination phase the cost effectiveness of malaria interventions decreases considerably. This study estimated the cost effectiveness of various strategies to combat malaria in preelimination and elimination phases in Iran. Methods: running costs of the interventions at each level of intervention was estimated by using evidence and expert opinions. The effect of each intervention was estimated using the documentary evidence available and expert opin- ions. Using a point estimate and distribution of each variable the sensitivity was evaluated with the Monte Carlo method. Results: The most cost-effective interventions were insecticide treated net (ITN), larviciding, surveillance for diag- nosis and treatment of patients less than 24 hours, and  indoor residual spraying (IRS) respectively, No related evi - dence found for the effectiveness of the border facilities. Conclusion: This study showed that interventions in the elimination phase of malaria have low cost effectiveness in Iran like many other countries. However ITN is the most cost effective intervention among the available interven- tions.